De novo hepatocellular carcinoma of liver allograft: A neglected issue. Issue 1 (1st February 2015) - Trevisani, Franco; Garuti, Francesca; Cucchetti, Alessandro; Lenzi, Barbara; Bernardi, Mauro
Highlights: De novo hepatocellular carcinoma after liver transplant is a rare event. Recurrence of liver disease in the allograft is a major risk factor for this tumor. This tumor generally occurs after a longer lapse of time than recurrence. Only molecular profiling techniques distinguish recipient origin from donor origin. Prevention relies on the effort to prevent/cure recurrent disease in the allograft. Abstract: De novo hepatocellular carcinoma (HCC) is a rare neoplasm, ensuing after liver transplantation. Its definitive identification requires sophisticated molecular analyses. Hence, some cases, particularly those ensuing in patients who have been transplanted with HCC, are probably misclassified as recurrences of the primary tumor. Nevertheless, a tumor recurrence cannot be excluded in patients transplanted without apparent malignancy, because of an occult HCC. The main risk factor for de novo HCC is the recurrence of hepatitis/cirrhosis in the allograft. All the described de novo HCCs occurred at least 2 years after OLT, whereas most recurrent HCCs develop within 2 years from surgery. The treatment of this tumor can follow the recommendations of guidelines for primary HCC and, unlike recurrent HCC, re-transplant can be considered a therapeutic option for these patients. Prevention of this tumor relies on the prevention/cure of recurrent liver disease in the allograft and on judicious post-transplant immunosuppression. The present review analyzes this topic by addressing seven key questions. An algorithm based on clinical factors – regarding primary and secondary tumors – to trigger the suspicion of de novo origin of a post-transplant HCC is proposed.